Titanium Ions Promote Exogenous Calcium-Dependent Calcium Influx in Activated Jurkat T Cells: A Possible Mechanism to Explain Its Immunostimulatory Properties - Chen, Jing; Li, Qiuying; Pang, Zhenhua; Gong, Ming; Tang, Li (Mediators of Inflammation, 2018)
Titanium and its alloys have been widely used in dental and orthopedic implants. Owing to the biotribocorrosion behavior of implants in simulated oral environment, Ti(IV) ions could be released into surrounding tissues. Current studies have found that Ti(IV) ions could affect the biological activities of immune cells in adjacent tissues and subsequently jeopardize the long-term performance of implant prostheses. However, the potential mechanism underlying its immunomodulatory properties remains unclear. Calcium signaling has been confirmed to be involved in regulation of lymphocyte immune function. Therefore, we hypothesize that Ti(IV) ions modulated T cell function through the change of intracellular calcium concentrations. This study is aimed at exploring the role of intracellular calcium responses in the modulatory effect of Ti(IV) ions on unactivated and phytohemagglutinin-activated Jurkat T cells. Here, we confirmed that Ti(IV) ions within a certain concentration range induced CD69 expression on both unactivated and activated T cells in our study. Additionally, the combined stimulation with Ti(IV) ions and PHA increased expression of IL-1β, TNF-α, and RANKL. Furthermore, we found that treatment with Ti(IV) induced a transitory increase in the levels of [Ca2+]i in activated Jurkat cells, dependent on the presence of exogenous calcium. Treatment with different doses of Ti(IV) for 24 h significantly increased the levels of [Ca2+]i in the activated Jurkat cells in a dose-dependent manner, but had little effect in the unactivated cells. Treatment with Ti(IV) did not significantly affect the PLCγ1 activation and inositol-1,4,5-trisphosphate (IP3) secretion in Jurkat cells. Taken together, these data indicated that Ti(IV) enhanced calcium influx during the T cell activation, independent of IP3-mediated intracellular calcium release. Our work provides insights into the mechanism involved in the regulation of lymphocyte behaviors under the effect of Ti(IV) ions, which may help to develop therapeutic strategies for dental implant failures.